KEMAMPUAN PENALARAN MATEMATIS: SYSTEMATIC LITERATURE REVIEW (Universitas PGRI Sumatera Barat, 2022)
Mathematical reasoning ability is one of the important learning objectives of mathematics to be achieved by students at school. This study aims to analyze qualitative studies on mathematical reasoning abilities conducted in the period 2015-2021. The method used is a Systematic Literature Review (SLR) on all qualitative research articles indexed in Google Scholar, Semantic, and ERIC. The search strategy was adapted to the selection criteria and used the PRISMA protocol as a guide for the research instrument. The variables involved in this study are the year of publication, education level, research class, demographics, journal indexer, material analyzed, and type of reasoning ability used. All data obtained are presented in a quantitative descriptive. The results of the SLR research show that studies related to students' mathematical reasoning abilities are widely published in 2020 and 2021. The majority of these studies are carried out at the junior high school level in grade VIII. The study was also dominated in Java & Bali on geometry and algebra materials. Suggestions for future educators or researchers to do more research on mathematical reasoning skills from the elementary school level, in areas outside Java & Bali, on materials other than algebra and geometry as well as research-related aspects of proof.